A characteristic curve including hygrothermal effects for predicting the failure of composite multi-bolt joints. (December 2022) - Shan, Meijuan; Zhang, Ruifeng; Liu, Fengrui; Zhao, Libin
Abstract: A characteristic curve that considers hygrothermal effects was developed based on the traditional characteristic curve. A nondimensional temperature was introduced to represent the severity of seven hygrothermal conditions experienced by primary aircraft structures. The tensile characteristic lengths and compressive characteristic lengths under the seven conditions were determined using a numerical strategy. Expressions between the characteristic lengths and the nondimensional temperature were established by fitting the data with exponential functions. Consequently, an equation of the characteristic curve formulated as a function of the nondimensional temperature and the angle, was established. The developed characteristic curve can be used to predict the failure of composite multi-bolt joints under any hygrothermal environment. Graphical abstract: Image 1 Highlights: A characteristic curve that considers hygrothermal effects was developed. A nondimensional temperature was used to represent the severity of the environmental conditions. The relation between the characteristic length and nondimensional temperature was expressed as an exponential function. The developed characteristic curve can predict the failure of composite multi-bolt joints in any hygrothermal environment.